Hemin levels in culture medium of Porphyromonas (Bacteroides) gingivalis regulate both hemin binding and trypsinlike protease production. - Carman, R J (1990)
Washed cells and Sarkosyl-insoluble outer membrane preparations of the black-pigmented bacteroides Porphyromonas gingivalis W50 bound hemin. The amount of hemin removed from a buffered solution by both cells and outer membranes was significantly larger if bacteria had been grown in broths supplemented with 5 mg of hemin per liter rather than none. Conversely, cells grown without supplemental hemin bound relatively little. However, all preparations bound some hemin. In addition, hemin regulated the production of significantly higher levels of trypsinlike protease by P. gingivalis W50. The nonpigmented variant, W50 BE1, showed no such responses to the levels of hemin in the growth medium.